Addressing the gender pay gap: Government and social partner actions - Ponzellini, Anna Maria; Aumayr, Christine; Wolf, Felix (Dublin, 2010)
"Wage differentials between men and women across Europe are a major policy concern for the European Commission and the social partners. This report provides an overview of national studies on the gender pay gap, and examines the policies and actions of governments and social actors to combat pay discrimination. The report first reviews quantitative and qualitative studies on the unadjusted and adjusted pay gap and examines the many factors cited to explain the wage differentials. Then it explores specific actions carried out by governments to reduce the gender pay gap, such as legislative measures, general recommendations, monitoring procedures and suppport for low-paid occupations. It also looks at joint initiatives and collective bargaining undertaken by the social partners, as well as highlighting successful good practice examples."